Evaluating the effect of policy prohibiting body checking on physical contacts in U15 and U18 youth ice hockey leagues - Kolstad, A. T.; Chin, M.; Martinez, G.; Janzen, L.; Krolikowski, M.; Goulet, C.; Nadeau, L.; Hagel, B. E.; Emery, C. A. (Clinical Journal of Sport Medicine, 2022)
Objective: To compare physical contacts (PCs) and head contacts (HCs) in nonelite U15 (ages 13-14) and U18 (ages 15-17) ice hockey players in body checking (BC) and non-BC leagues. Design: Cohort video analysis study. Setting: Ice hockey arenas in Calgary, Canada. Participants: Players from 13 BC and 13 non-BC games at the nonelite U15 and U18 levels (n = 52 total games). Assessment of Risk Factors: Games were videotaped and analyzed to compare PC variables between leagues allowing and prohibiting BC. Main Outcome Measures: Validated methodology for PC type (trunk PC and other types of PC with limb/stick/head), intensity (low and high intensity), and HC. Incidence rate ratios (IRRs) were estimated using Poisson regression (controlling for cluster by team game and offset by player minutes) to compare the incidence of PCs in BC and non-BC games. Results: The rate of trunk PCs was lower in the non-BC leagues for both U15 (IRR = 0.50, 99% confidence interval [CI]: 0.43-0.58) and U18 (IRR = 0.56, 99% CI: 0.46-0.67) players. This was most significant for BC contacts (U15: IRR = 0.18, 99% CI: 0.11-0.29; U18: IRR = 0.16, 99% CI: 0.08-0.34), although also significant for body contacts (U15: IRR = 0.54, 99% CI: 0.46-0.64; U18: IRR = 0.58, 99% CI: 0.48-0.70), other PCs, (U15: IRR = 0.60, 99% CI: 0.45-0.78; U18: IRR = 0.71, 99% CI: 0.58-0.88), and HCs (U15: IRR = 0.40, 99% CI: 0.22-0.71; U18: IRR = 0.37, 99% CI: 0.25-0.57). Conclusions: The incidence of BC was 82% lower in the U15 and 84% lower in U18 levels not allowing BC, with lower HC and other PC rates also in non-BC leagues. These findings demonstrate high adherence with BC policy change in youth ice hockey.